2013
DOI: 10.1017/s0004972713000890
|View full text |Cite
|
Sign up to set email alerts
|

Finite Higher Commutators in Associative Rings

Abstract: If T is any finite higher commutator in an associative ring R, for example, T = [[R, R], [R, R]], and if T has minimal cardinality so that the ideal generated by T is infinite, then T is in the centre of R and T 2 = 0. Also, if T is any finite, higher commutator containing no nonzero nilpotent element then T generates a finite ideal.2010 Mathematics subject classification: primary 16W10; secondary 16R50, 16D25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…H. Bell [5] has proved that if I is a nonzero right ideal of finite index in a prime ring R and OEI; I is finite, then R is either finite or commutative (see also [17,Corollary 1.2]). C. Lanski [16] has showed that if T is a finite higher commutator of R containing no nonzero nilpotent element, then T generates a finite ideal of R.…”
Section: Introductionmentioning
confidence: 99%
“…H. Bell [5] has proved that if I is a nonzero right ideal of finite index in a prime ring R and OEI; I is finite, then R is either finite or commutative (see also [17,Corollary 1.2]). C. Lanski [16] has showed that if T is a finite higher commutator of R containing no nonzero nilpotent element, then T generates a finite ideal of R.…”
Section: Introductionmentioning
confidence: 99%